Skeletal muscle atrophy‐induced hemopexin accelerates onset of cognitive impairment in Alzheimer's disease. Issue 6 (17th October 2021) - Nagase, Tsukasa; Tohda, Chihiro
Abstract: Background: Alzheimer's disease (AD) is an unmet medical need worldwide, and physical inactivity is a risk factor for AD. Performing physical exercise is difficult at old age, and thus, decline in physical movement may be a cause of age‐associated lowering of the brain function. This study aimed to elucidate the molecular mechanism and onset of the skeletal muscle atrophy‐induced acceleration of AD. Methods: Pre‐symptomatic young 5XFAD or non‐transgenic wildtype mice were used. The bilateral hindlimbs were immobilized by placing them in casts for 14 days. Cognitive function was evaluated using the object recognition and spatial memory tests. Further, the hindlimb muscles were isolated for organ culture. Conditioned media (CM) of each muscle was separated by two‐dimensional polyacrylamide gel electrophoresis (2D‐PAGE). Protein expressions in the CM were analysed by matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry analysis. The expression levels of candidate proteins were quantified using ELISA. After continuous intracerebroventricular (i.c.v.) infusion of recombinant hemopexin, cognitive function was evaluated. Gene microarray analysis of the hippocampus was performed to investigate the molecules involved in the accelerated memory deficit. Real‐time reverse transcription polymerase chain reaction and histological analysis confirmed the expression. Results: Casting for 2 weeks reduced skeletal muscle weight. Object recognition memory in the cast‐attached 5XFAD mice ( n = 7, training vs. test, P = 0.3390) was impaired than that in age‐matched wildtype ( n = 7, training vs. test, P = 0.0523) and non‐cast 5XFAD mice ( n = 7, training vs. test, P = 0.0473). On 2D‐PAGE, 88 spots were differentially expressed in muscle CM. The most increased spot in the cast‐attached 5XFAD CM was hemopexin. Hemopexin levels in the skeletal muscle ( n = 3, P = 0.0064), plasma ( n = 3, P = 0.0386), and hippocampus ( n = 3, P = 0.0164) were increased in cast‐attached 5XFAD mice than those in non‐cast 5XFAD mice. Continuous i.c.v. infusion of hemopexin for 2 weeks induced memory deficits in young 5XFAD mice ( n = 4, training vs. test, P = 0.6764). Lipocalin‐2 ( Lcn2 ) messenger RNA (mRNA), neuroinflammation‐associated factor, was increased in the hippocampus in hemopexin‐infused 5XFAD mice than in control mice. LCN2 protein in the hippocampus was localized in the neurons, but not glial cells. Lcn2 mRNA levels in the hippocampus were also increased by cast‐immobilization of the hindlimbs ( n = 6, P = 0.0043). Conclusions: These findings provide new evidence indicating that skeletal muscle atrophy has an unbeneficial impact on the occurrence of memory impairment in young 5XFAD mice, which is mediated by the muscle secreted hemopexin.